2015
DOI: 10.1088/1367-2630/17/8/082002
|View full text |Cite
|
Sign up to set email alerts
|

Kapitza–Dirac effect with traveling waves

Abstract: We report on the possibility of diffracting electrons from light waves traveling inside a dielectric medium. We show that, in the frame of reference which moves with the group velocity of light, the traveling wave acts as a stationary diffraction grating from which electrons can diffract, similar to the conventional Kapitza-Dirac effect. To characterize the Kapitza-Dirac effect with traveling light waves, we make use of the Hamiltonian Analogy between electron optics and quantum mechanics and apply the Helmhol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…For reviews on the subject, we refer to [22,23]. Moreover, recent studies on spininsensitive KD scattering may be found in [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For reviews on the subject, we refer to [22,23]. Moreover, recent studies on spininsensitive KD scattering may be found in [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction of electrons in a standing wave of light as proposed by Kapitza and Dirac [1] has been demonstrated at the beginning of the century [2,3], with analogs by diffracting into multiple diffraction orders [4] or by using atoms [5,6]. The Kapitza-Dirac effect has already been studied theoretically, for example in adiabatic switching [7], by using perturbation theory [8][9][10], for spinless particles by using the Klein-Gordon equation [11,12], for the case of a traveling wave in a dielectric medium [13] or for a blazed, sawtooth-shaped grating [14]. See also [15] for an overview.…”
Section: Introductionmentioning
confidence: 99%
“…Here only the difference with the known results is in the physical characteristic "group velocity of light" which is a rough mistake repeated also in the text, even for a monochromatic wave. As it has been shown above, diffraction effect is thoroughly the result of the phase relations and is conditioned exceptionally by the phase velocity of light that must be smaller than c. Beside this incorrectness, authors of this paper [6] ignored the existence of critical field in this process and influence of considered phenomenon of a particle "reflection" or capture on the diffraction effect, meanwhile one of these authors is also a co-author of both inelastic diffraction effect [9] and "reflection" phenomenon in the undulators [15]. Concerning the citation of considering papers devoted to diffraction effect on a travelling wave, these mechanically are included in the list of References of the paper [6] in irrelevant context by footnote: "see, for example...".…”
mentioning
confidence: 83%
“…Note that considered effect of electrons inelastic diffraction takes place at the fulfilment of classical resonance condition Eq. (6). The latter is valid if the quantum recoil of an electron because of photons absorptionradiation processes can be neglected.…”
mentioning
confidence: 99%